Vere risonanze elusive: la poetica del compositore Federico Incardona nello specchio di Maldoror riflesso da Bachelard (Altre Modernità, 2012)
The musical poetics of the composer Federico Incardona (Palermo, 1958-2006) reveals deep affinities with the Chants de Maldoror by Isidore Ducasse. The method used to identify and analyze these affinities is an inter-disciplinary triangulation, linking music and poetry through the psychological and philosophical reading of the Chants given by Gaston Bachelard in his essay of 1939. The “active” poetry of Lautréamont, his “cinétisme”, his “dynamogénie” are reflected in the Incardonian idea of composition as transmutation of living bodies into sound. This is achieved by a treatment of timbre, articulation and intensity extremely mobile, “alive”, and by a tempo that combines an exhausted slowness with an aggressive, almost animal rapidity. The very act of composition can be conceived, in analogy to hunting, such as “capture” of sounds, in particular thanks to the twelve-tone device. The “complex of Lautréamont” is a phenomenon inextricably psychological and cultural; so also in Incardona adolescence is transformed from existential motive into artistic motif. Starting from the case of Lautréamont, Bachelard formulates a general poetics of metamorphosis, which extends validly in music, especially in the informal writing of Incardona. Finally, Lautréamont is useful to Bachelard for grafting, onto the “living” basis of writing, cultural and intellectual values??; Incardona as well, intending music as “night mathematics”, combines construction and expression, emotion and serial structure.